Resiliensi Remaja Ditinjau Dari Tipe Temperamen dan Adversity Quotient (AQ) - Lailatuzzahro Al-Akhda Aulia; Estalita Kelly (Ilmu Psikologi Universitas Yudharta Pasuruan)
This research conducted to know whether or not the differences adolescents resi-lience when viewed from temperament types and AQ in SMAN 1 Purwosari Pasuruan. The sampling technique used cluster stratified random sampling. Data collected used temperament scale, AQ profile test, and resilience scale. Resilience scale with coefficient of point-biserial correlation between 0,30 to 0,50 and coefficient of reliability by 0,751. While the temperament scale (Ummah, 2010), for the type of temperament koleris with coefficient of point-biserial correlation between 0,33 to 0,49 and coefficient of reliability by 0,624. The type of temperament phlegmatic with coefficient of point-biserial correlation between 0,34 to 0,65 and coefficient of reliability by 0,776. The type of temperament sanguinis with coefficient of point-biserial correlation between 0,35 to 0,94 and coefficient of reliability by 0,824. The type of temperament melancholy with coefficient of point-biserial correlation between 0,31 to 0,78 and coefficient of reliability by 0,701. The data when calculated with variance analysis two lines. This result proof that types of temperament influence adolescents’ resilience are accepted at 1% significance level, where FoA by 3,91 is greater than F tab 1% by 3,78. AQ also influence adolescents’ resilience are accepted at 1% significance level, where FoB by 6,63 is greater than F tab 1% by 4,61.